High purity recombinant human growth hormone (rhGH) expression in Escherichia coli under phoA promoter. Issue 2 (4th March 2017) - Song, Hao; Jiang, Jingxin; Wang, Xuedong; Zhang, Jianguo
ABSTACT: Recombinant human Growth Hormone (rhGH) is an important protein for human growth and is in high demand in clinics. Hence, it is necessary to develop an efficient fermentation process to produce highly pure rhGH. In this study, rhGH was expressed in Escherichia coli under alkaline phosphatase ( phoA ) promoter. The cultivation conditions for high expression level and purity of rhGH were investigated. The best initial phosphate concentration for rhGH expression, out of the 4 levels of initial phosphate concentration tests performed, was 12.6 mmol/L. Subsequently, 2 fed-batch cultivations under low dissolved oxygen (DO) (0% – 10%) and high DO (20% – 30%) conditions were carried out. High purity rhGH (92%) was obtained from 20% – 30% DO-stat cultivation, although the biomass did not show any significant difference. In summary, this research provided an efficient fermentation process for high purity rhGH production from E. coli under phoA promoter, which can lower the production and purification costs for large-scale production of rhGH.